Relationship between situational determinants of teachers’ perceptions of organisational politics and job satisfaction - Manasseh Morongoa Mokgolo; Maoka Andries Dikotla (South African Journal of Education)
With the study reported on here we aimed to explore the relationship between situational determinants of teachers’ perceptions of organisational politics in some public high schools in the KwaZulu-Natal province. We adopted a cross-regional survey design and convenience sampling to study teachers (n = 301) at public high schools in all 10 districts in KwaZulu-Natal, South Africa. We found that perceived organisational politics had a positive relationship to job satisfaction. Analyses of correlational and stepwise regression showed numerous significant relations between the perceptions of organisational politics and job satisfaction variables. The results of the study can be used by the Department of Basic Education to improve South African provincial school management practices for the development and retention of experienced and valuable educators.